Highlights of the life of Nikolai Iosifovich Boikov (1873-1959) - Druzhinina, Inna (project baikal, 2023)
The purpose of the article was to restore the memory of the famous Irkutsk architect, teacher and scientist. The year 2023 marks the 150th anniversary of the talented architect. Some facts of his biography and creative path became especially important milestones in the fate of this man. The study is based on archival materials of the Irkutsk Regional Organisation of the Union of Architects of Russia. The authenticity of the materials is confirmed by the fact that the documents in the archive appeared thanks to the relatives of N. I. Boikov. The work with archival documents prompted the author to study in more depth the materials on little-known projects of N. I. Boikov, to conduct their field research, interviews with the plant staff and local residents. Many biographical facts and highlights of N. I. Boikov’s creative life are published for the first time.
Keywords: Boikov N. I.; provincial architect; engineer; teacher; researcher; Union of Architects of the USSR; Komzhilstroy; Fundamentstroy; Iroblproekt